Reservas internacionais revisitadas: Novas estimativas de patamares ótimos - Christian Vonbun (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper shows estimates of the optimal level of foreign reserves for Brazil between the first quarter of 2004 and the third trimester of 2012, by applying the new Jeanne e Rancière (2011) framework, using different scenarios. The estimates of the optimal holdings of this asset are calculated for several feasible scenarios. Our results suggest that, under various alternative scenarios and assumptions regarding the model's main parameters, the observed level of reserves in Brazil has become above the optimal level, thereby generating high and increasing costs for the Brazilian government and tax payers.
Keywords: E63; F31; F32; F34; F40; F41; G11; 330; international reserves; macroeconomics; external debt; sudden stops